Mufti Muhammad Taqi 'Usmani and his scholarly contribution to the Qur’anic studies - Nawi, Zaharudin; Mohd. Marzuki, Zunaidah (Faculty of Islamic Civilisation Studies, International Islamic University College Selangor (KUIS), Malaysia, 2017)
Mufti Taqi Usmani of Pakistan is one of the most prominent contemporary Muslim scholars from Deobandi School of Thought. He is not only a leading living scholar of Islamic Jurisprudence and Islamic finance, but also a scholar and an intellectual of the Qur´Én, the Hadith, Islamic law, and comparative religion. He has always been placed among top fifty in “The 500 Most Influential Muslims” in the world since 2009 until 2016. His works on the sciences of Qur´Én and the interpretation of the Holy Qur´Én show his scholarship in this field. The writing of “UlËm Al-Qur´Én” (An Approach to the Qur´Énic Sciences in Urdu), “The Meanings of the Noble Qur´Én” (English translation of the Quran) and “ÓsÉn Tarjamah Qur´Én” (The simple translation of the Qur´Én with notes in Urdu) are his major works in the field of Qur´Én. His supervision of translating the “MaÑÉriful Qur´Én” of his father, MaulÉnÉ Mufti SyafÊÑ, from Urdu to English is considered as his magnificent endeavor and contribution to this field. This paper aims to discover the biography of Mufti TaqÊ UsmÉnÊ and his scholarly contribution towards the interpretation of the Holy Qur´Én in the above-mentioned works.